(untitled) (Global Journal of Science Frontier Research, 2014)
This paper assessed the signal strength of GSM network service providers in Kwara State Polytechnic permanent site and Ara village. The latitude, longitude and elevation of the two reference locations where the study would be carry out were picked with Global Positioning System. The first location was at the gate of Kwara State Polytechnic permanent site at latitude 08 0 32 1 37.6 11 and longitude 04 0 38 1 07.7 11 and Ara village at latitude 08 0 34 1 27.9 11 and longitude 04 0 38 1 17.3 11 with elevation of 350 and 364 meters respectively. The signal strength of MTN, GLO, AIRTEL and ETISALAT networks were measured with TECNO D3 Android mobile receiver from the Base Transceiver Station (BTS) at intervals of 100 meters. The measured data were analysed graphically and compared with each other to see the performance of each of the GSM network operators in the study area. The results revealed that the performance of these network providers are yet to be adjudged satisfactory.